European League Against Rheumatism recommendations for the management of psoriatic arthritis with pharmacological therapies. Issue 1 (27th September 2011) - Gossec, L; Smolen, J S; Gaujoux-Viala, C; Ash, Z; Marzo-Ortega, H; van der Heijde, D; FitzGerald, O; Aletaha, D; Balint, P; Boumpas, D; Braun, J; Breedveld, F C; et al.
Abstract : Background: Psoriatic arthritis (PsA) is a clinically heterogeneous disease. Clear consensual treatment guidance focused on the musculoskeletal manifestations of PsA would be advantageous. The authors present European League Against Rheumatism (EULAR) recommendations for the treatment of PsA with systemic or local (non-topical) symptomatic and disease-modifying antirheumatic drugs (DMARD). Methods: The recommendations are based on evidence from systematic literature reviews performed for non-steroidal anti-inflammatory drugs (NSAID), glucocorticoids, synthetic DMARD and biological DMARD. This evidence was discussed, summarised and recommendations were formulated by a task force comprising 35 representatives, and providing levels of evidence, strength of recommendations and levels of agreement. Results: Ten recommendations were developed for treatment from NSAID through synthetic DMARD to biological agents, accounting for articular and extra-articular manifestations of PsA. Five overarching principles and a research agenda were defined. Conclusion: These recommendations are intended to provide rheumatologists, patients and other stakeholders with a consensus on the pharmacological treatment of PsA and strategies to reach optimal outcomes, based on combining evidence and expert opinion. The research agenda informs directions within EULAR and other communities interested in PsA.